Comprehensive analysis of peripheral dose in electron beam therapy with a Varian TrueBeam Linac - Kapil Dev Maharaj; Mahsheed Sabet; Joshua Dass; Mounir Ibrahim; Talat Mahmood; Pejman Rowshanfarzad (Radiation Medicine and Protection)
Objective: To investigate the characteristics of peripheral doses outside electron-beam applicators in Varian TrueBeam linacs. Method: Peripheral doses outside the electron applicator were measured for 6-, 9- and 12-MeV beams at the maximum dose depth (Dmax) for each energy source and at a source-to-surface distance (SSD) of 100 cm. Measurements were performed using EBT3 films in solid water phantoms. The impact of field size on the penumbra width and peripheral doses was studied using various cutouts, including 3 ​cm ​× ​3 ​cm, 6 ​cm ​× ​6 ​cm, and 10 ​cm ​× ​10 ​cm in a 10 ​cm ​× ​10 ​cm applicator with the gantry and collimator at 0°. The influence of the applicator size was investigated using a circular cutout of 5 ​cm in diameter for various applicator sizes, including 6 ​cm ​× ​6 ​cm, 10 ​cm ​× ​10 ​cm, 15 ​cm ​× ​15 ​cm, 20 cm ​× ​20 ​cm, and 25 ​cm ​× ​25 ​cm, at Dmax for each energy, while keeping the gantry and collimator angle at 0°. The measured dose profiles were compared with the Eclipse treatment planning system (TPS) predicted dose profiles. The effect of varying gantry angles (0°, 90°, and 270°) for a 3 ​cm ​× ​3 ​cm cutout in a 10 ​cm ​× ​10 ​cm applicator for each energy source and varying collimator angles (0°, 90°, and 270°) for a 10 ​cm ​× ​10 ​cm field were investigated to determine their effects on the penumbra widths and peripheral doses. Results: Both the penumbra width and peripheral dose values increased with energy across different field sizes, gantry angles, collimator angles, and applicator sizes. Root mean square deviation (RMSD) analysis indicated minimal differences between the measured profiles and TPS data. Peripheral doses remained below 5% of the maximum dose approximately 10–15 ​mm away from the field edges, suggesting the potential for implementing additional shielding where required. Conclusions: This study highlights the importance of considering peripheral doses in electron radiotherapy. It is important to note the impact on healthy tissues beyond the treatment area to ensure patient safety and prevent the long-term side effects of treatment. These findings emphasize the necessity of implementing appropriate measures to minimize peripheral doses.